International medical students' expectations and worries at the beginning of their medical education: a qualitative focus group study. Issue 1 (December 2016) - Huhn, Daniel; Huber, Julia; Ippen, Franziska; Eckart, Wolfgang; Junne, Florian; Zipfel, Stephan; Herzog, Wolfgang; Nikendei, Christoph
Abstract Background The number of international students has increased substantially within the last decade. Due to cultural barriers, this specific group faces diverse challenges. In comparison to German colleagues, international medical students perform significantly lower in clinical examinations and exceed the average duration of study; they suffer from personal distress as well as insufficient support. Within the present study, their individual perspectives, expectations, hopes and fears were examined. Methods Four focus groups with first-year international medical students (N  = 16) were conducted in October 2013. Each 60- to 90-min discussion was audiotaped, transcribed and analysed using qualitative methods. Results International medical students go abroad in search of good study-conditions. For the choice of place of study, affordability, social ties as well as an educational system following the achievement principle are decisive factors. While contact with German-students and other international students is seen as beneficial, international medical students are most concerned to encounter problems and social exclusion due to language deficits and intercultural differences. Conclusions Facilitating the access to university places, the provision of financial aid and, moreover, social support, nurturing cultural integration, would greatly benefit international medical students. Hereby, the establishment of specific medical language courses as well as programs fostering intercultural-relations could prove to be valuable.